2021
DOI: 10.1002/jmri.27740
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Disruption of Dynamic Functional Network Connectivity in Patients With Hepatitis B Virus‐related cirrhosis

Abstract: Background: The diseased-related dynamic functional network connectivity (dFNC) disruption and its relationship with cognitive impairment in hepatitis B virus-related cirrhosis (HBV-RC) patients with minimal hepatic encephalopathy (MHE) and no MHE (NMHE) remain unknown. This knowledge would help identify MHE pathophysiology and monitor disease progression in HBV-RC patients. Purpose: To investigate the dFNC in patients with NMHE and MHE and the relationship between dFNC indices with the psychometric hepatic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…The similarity between windowed functional connectivity matrices was calculated using the default distance measures (sqEuclidean distance). It has been proven to be an effective measure for high-dimensional data (Lin et al, 2021 ; Xu et al, 2022 ). Furthermore, we performed a cluster validity analysis to evaluate the optimal number of states based on three criteria (Silhouette, Davies-Bouldin values, and Calinski – Harabasz), and the maximum number of states allowed to estimate was set at 10.…”
Section: Methodsmentioning
confidence: 99%
“…The similarity between windowed functional connectivity matrices was calculated using the default distance measures (sqEuclidean distance). It has been proven to be an effective measure for high-dimensional data (Lin et al, 2021 ; Xu et al, 2022 ). Furthermore, we performed a cluster validity analysis to evaluate the optimal number of states based on three criteria (Silhouette, Davies-Bouldin values, and Calinski – Harabasz), and the maximum number of states allowed to estimate was set at 10.…”
Section: Methodsmentioning
confidence: 99%
“…The preprocessing of rs-fMRI data was performed using the Statistical Parametric Mapping 12 (SPM12) software package and the Data Processing Assistant for Resting-State fMRI (DPARSF) [ 35 ] as in our previous work [ 21 , 36 ]. The main steps were as follows: (1) we removed the first 10 time points to allow for signal equilibration; (2) we performed slice-timing correction and motion correction; and (3) we applied spatial normalization to the Montreal National Institute space (MNI) and smoothing using a 6 mm full-width at high maximum (FWHM) Gaussian kernel.…”
Section: Methodsmentioning
confidence: 99%
“…One can consider dFNC to be more specific than static FC because it unpacks temporal features otherwise averaged in static FC measures [ 24 – 26 ]. dFNC has been successfully used to investigate the dynamic functional modulations in patients with schizophrenia [ 20 ], patients with hepatic encephalopathy [ 21 ], and healthy aged subjects [ 22 ]. However, no study has been conducted to uncover the relationship between dFNC and suicidality in MDD.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, resting-state functional MRI (rs-fMRI) has been widely used to investigate macroscopic neural phenotypes of cognitive deterioration in HBV-RC patients from the NMHE stage to MHE stage. [7][8][9] Combining rs-fMRI and large-scale graph-theoretical methods, Jao et al 7 demonstrated that brain networks in HBV-RC patients were progressively more random, less clustered, and less modular as the disease advanced from NMHE to OHE, while the topological centrality and functional connections between nodes were progressively reorganized. Lin et al 8 focused on the functional connectivity (FC) between the hippocampus and other brain regions and found that the FC of the left hippocampus (LHP), the bilateral posterior cingulate gyri of the LHP and the left angular gyrus (LAG) and of the right hippocampus (RHP), and the bilateral medial frontal cortex (MFC) gradually decreased in the progression from NMHE to MHE.…”
mentioning
confidence: 99%
“…In the past decade, resting‐state functional MRI (rs‐fMRI) has been widely used to investigate macroscopic neural phenotypes of cognitive deterioration in HBV‐RC patients from the NMHE stage to MHE stage 7–9 . Combining rs‐fMRI and large‐scale graph‐theoretical methods, Jao et al 7 demonstrated that brain networks in HBV‐RC patients were progressively more random, less clustered, and less modular as the disease advanced from NMHE to OHE, while the topological centrality and functional connections between nodes were progressively reorganized.…”
mentioning
confidence: 99%